From traits to daily experiences: An adaptation of the Selflessness/Self-centeredness Inventory to day-level assessment - Lucas David; Nicolas Pellerin; Michael Dambrun (PLoS ONE, 2026)
Conceptualized as distinct psychological functionings respectively linked to authentic-durable and fluctuating happiness, selflessness and self-centeredness have recently been the subject of instrument development to evaluate their manifestations at the trait-level. Along the lines of this work, the goal of the current research was to adapt the psychometric instrument at the day-level: the Selflessness/Self-centeredness Inventory – Day-level (SSI-D). Consistent with the trait-version, both exploratory analysis (Study 1, N = 853) and confirmatory analysis (Study 2, N = 265) indicated that the SSI-D measured seven factors organized into two latent variables (i.e., selflessness divided into four components, self-centeredness divided into three dimensions). Correlational analysis (Study 3, N = 1409) provided initial evidence that day-level selflessness and self-centeredness can be differentiated psychometrically and showed theoretically meaningful patterns of association with mental health, interpersonal health, and pro-environmental outcomes. Invariance analyses were satisfactory, and preliminary validity evidence was generally consistent with theoretical expectations, although further validation using more comprehensive and jointly administered criterion measures is needed.